1999
DOI: 10.1097/00005537-199902000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Biological Efficacy of an Adeno‐Associated Virus Vector–Cystic Fibrosis Transmembrane Regulator (AAV‐CFTR) in the Cystic Fibrosis Maxillary Sinus

Abstract: AAV-CFTR administration to the maxillary sinus results in successful, dose-dependent gene transfer to the maxillary sinus and alterations in sinus TEPD suggestive of a functional effect, with little or no cytopathic or host immune response. Further study is warranted for AAV vectors as they may prove useful for CFTR gene transfer and other in vivo gene transfer therapies. A prospective, randomized, double-blind, placebo-controlled, within-subjects, phase II clinical trial of the effect AAV-CFTR on clinical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(99 citation statements)
references
References 18 publications
2
97
0
Order By: Relevance
“…3 Numerous studies have demonstrated promise for AAV as a safe and efficient vector in preclinical and clinical trials. [4][5][6] However, there have not been any significant efforts dedicated to understanding the impact of strain background and predisposition to autoimmunity on AAVmediated gene transfer. In the current study, we investigated the immune responses against AAV2 capsids and transgene products following intramuscular delivery of AAV2 vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Numerous studies have demonstrated promise for AAV as a safe and efficient vector in preclinical and clinical trials. [4][5][6] However, there have not been any significant efforts dedicated to understanding the impact of strain background and predisposition to autoimmunity on AAVmediated gene transfer. In the current study, we investigated the immune responses against AAV2 capsids and transgene products following intramuscular delivery of AAV2 vectors.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Several clinical trials utilizing AAV for the treatment of cystic fibrosis, hemophilia, prostate cancer and muscular dystrophy are underway, with early evidence of human clotting factor IX production in hemophilia B patients. [4][5][6] In spite of its acknowledged safety, AAV has recently produced surprises in the field of gene therapy. Traces of AAV have been observed in treated patient's semen, and liver tumors of uncertain cause have been found in diseased mice treated with AAV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] These vectors have a proven safety profile and the ability to elicit a minimal inflammatory response in comparison with other gene transfer agents. [34][35][36][37] To increase lung-specific delivery and promote high levels of gene expression, we used an AAV5 pseudotyped vector for efficient airway transduction [38][39][40] and the CMV (Cytomegalovirus)/chicken-b-actin hybrid (Cb) promoter, a promoter with robust activity in the murine lung. 41 Using these elements, we hypothesized that AAV-based gene transfer of IL-10 would result in high levels of lung-specific IL-10 expression, ameliorating the excessive response in the lung without systemic immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…9 Many of the investigations using rAAV have concentrated on serotype 2 (rAAV2), which demonstrates a wide tissue tropism and persistent gene expression in various animal species. As a result, several clinical trials involving rAAV2 vectors have been initiated, most notably involving patients with cystic fibrosis (CF) [10][11][12] and hemophilia. 13 Studies using vectors pseudotyped with the capsid proteins of other known serotypes (e.g.…”
Section: Introductionmentioning
confidence: 99%